(untitled) (Medical Forum Monthly, 2021)
Objective: To find the genetic correlation in twins and caries by accessing DMFT index. Study Design: Cross-sectional study Place and Duration of Study: This study was conducted at the department of conservative dentistry, College of Dentistry, Qassim University for a period of 03 months from January to March 2019. Materials and Methods: A total of 25 pairs of twins were examined in the study. Data was analyzed by SPSS version 20.0. Mean values of each component of the DMFT index were calculated by using descriptive statistics, and comparison was made between male and female groups by using Pearson's correlation. Results: The comparison showed significant differences in decayed and overall DMFT scores between male and female groups. The comparison amongst each subgroup of male and female twins showed a positive genetic correlation in both subgroups of the twin. Conclusion: This study concluded that the DMFT index is a valid tool to determine caries. There was a significant difference in decayed and overall DMFT scores between the male and female twin groups. Also, there might be genetic influence to the carious disease process among the twins in both males and female subgroups.